Los Pronósticos Climáticos y la Toma de Decisiones en Agricultura - Norman E. Breuer; Clyde Fraisse; David Zierden (EDIS)
AE463, an 8-page illustrated fact sheet by Norman E. Breuer, Clyde Fraisse, and David Zierden, is the Spanish-language version of ABE352/AE267 Climate Forecast and Decision Making in Agriculture. It describes the type of strategic pre-season decision-making that should take into consideration climate forecasts, how climate is predicted, how to interpret the forecasts, the climate of Florida, and climate forecast applications to agriculture in Florida. Includes references. Published by the UF Department of Agricultural and Biological Engineering, June 2010.